Emotional Working Memory in Ageing and Anxiety - Hajonides van der Meulen, Jasper (Student Undergraduate Research E-journal!, 2015)
Altered processing of emotional information in ageing and anxiety can be detrimental for one’s well-being. A total of 97 participants were tested with a novel delayed match to sample task with positive and negative faces of different levels of emotional intensity. Results show less accurate recall of negative stimuli in anxiety while older adults showed a bias to rate negative faces as less negative. The relationship between emotional working memory and anxiety was not influenced by age. Anxiety and ageing both interfere with emotional working memory; interestingly, the results suggest unrelated effects on processing of negative stimuli in working memory.